2006
DOI: 10.1242/dev.02538
|View full text |Cite
|
Sign up to set email alerts
|

Man1, an inner nuclear membrane protein, regulates vascular remodeling by modulating transforming growth factor β signaling

Abstract: A growing number of integral inner nuclear membrane (INM) proteins have been implicated in diverse cellular functions. Man1, an INM protein, has recently been shown to regulate transforming growth factor (Tgf) ␤ superfamily signaling by interacting with receptor-associated Smads. However, the in vivo roles of Man1 have not been fully characterized. Here, we show that Man1 regulates vascular remodeling by analyzing Man1-deficient embryos lacking the Smad interacting domain. Man1-deficient embryos die at midgest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 46 publications
4
67
0
Order By: Relevance
“…In the course of analyzing Man1 ⌬/⌬ embryos, we found that most of the mutant embryos (31 of 32) had pericardial edema (Ishimura et al, 2006), suggesting that they had defective heart morphogenesis. We investigated the gross morphology of Man1…”
Section: Man1-deficient Embryos Exhibit Abnormal Heart Morphogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…In the course of analyzing Man1 ⌬/⌬ embryos, we found that most of the mutant embryos (31 of 32) had pericardial edema (Ishimura et al, 2006), suggesting that they had defective heart morphogenesis. We investigated the gross morphology of Man1…”
Section: Man1-deficient Embryos Exhibit Abnormal Heart Morphogenesismentioning
confidence: 99%
“…In cultured cells, overexpression of MAN1 inhibits TGF␤-responsive reporter activation and antagonizes the arrest of TGF␤-induced cell proliferation. In the Xenopus embryo, overexpression of XMAN1 inhibits dorsal mesoderm induction by TGF␤/activin/Nodal signaling (Ishimura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GT , showed that homozygous mutants die during embryogenesis (Ishimura et al 2006;Cohen et al 2007). The phenotypes of Man1 GT embryos suggest that lethality was due to hyperactivation of the TGF-b/BMP signaling pathway, resulting in an increased nuclear accumulation of phosphorylated Smad2/3 and changes in Smad target gene expression that increase extracellular matrix deposition and altered vascular remodeling.…”
Section: /Dman1mentioning
confidence: 99%